Cooperative Principle in Verbal Humour: Analysis of Arabic Podcast Short Films - Tsani, Muhammad Jaohar; Ramadhan, Aji Rizqi; Bariyyah, Isnaeni Khoerul; Al Farisi, Mohamad Zaka (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2024)
Communication is a crucial process in human interaction for exchanging information and maintaining social relationships. Grice's cooperative principle provides guidelines for effective communication, yet violations of this principle are often exploited to create humor. This study analyzes violations of the cooperative principle that generates verbal humor in short Arabic films on the YouTube channel Arab Podcasts. Using a qualitative approach with observation and note-taking methods, the researcher observes selected episodes to understand the context of the conversations and the humor that arises, then records examples of verbal humor. Data analysis is conducted in two stages: first, analyzing the application of Grice's four maxims, and second, identifying types of verbal humor based on Berger's theory. The results show that the most significant violations occur in the maxims of quality and relevance, each with three violations (33.33%). The most frequently occurring type of verbal humor is misunderstanding, with two instances (25%), followed by other types such as paradox and wordplay. This study provides insights into how verbal humor is generated through violations of the cooperative principle in the context of Arabic language conversations.